Red nucleus and rubrospinal tract disorganization in the absence of Pou4f1 - Martinez-Lopez, Jesus E.; Moreno-Bravo, Juan A.; Madrigal, M. Pilar; Martinez, Salvador; Puelles, Eduardo (Frontiers in Neuroanatomy, 2015)
The red nucleus (RN) is a neuronal population that plays an important role in forelimb motor control and locomotion. Histologically it is subdivided into two subpopulations, the parvocellular RN (pRN) located in the diencephalon and the magnocellular RN (mRN) in the mesencephalon. The RN integrates signals from motor cortex and cerebellum and projects to spinal cord interneurons and motor neurons through the rubrospinal tract (RST). Pou4f1 is a transcription factor highly expressed in this nucleus that has been related to its specification. Here we profoundly analyzed consequences of Pou4f1 loss-of-function in development, maturation and axonal projection of the RN. Surprisingly, RN neurons are specified and maintained in the mutant, no cell death was detected. Nevertheless, the nucleus appeared disorganized with a strong delay in radial migration and with a wider neuronal distribution; the neurons did not form a compacted population as they do in controls, Robo1 and Slit2 were miss-expressed. Cplx1 and Npas1, expressed in the RN, are transcription factors involved in neurotransmitter release, neuronal maturation and motor function processes among others. In our mutant mice, both transcription factors are lost, suggesting an abnormal maturation of the RN. The resulting altered nucleus occupied a wider territory. Finally, we examined RST development and found that the RN neurons were able to project to the spinal cord but their axons appeared defasciculated. These data suggest that Pou4f1 is necessary for the maturation of RN neurons but not for their specification and maintenance.